Caracterização genotípica e molecular de isolados clínicos de Pseudomonas aeruginosa resistentes a quinolonas - Ferreira, Sónia Cristina das Neves (2016)
Pseudomonas aeruginosa is a Gram-negative pathogen associated with a number of nosocomial infections. The preoccupying increase of quinolone resistant P. aeruginosa was the basis for the present study. Thirty five quinolone resistant P. aeruginosa strains were obtained from the pathology service of Hospital Infante D. Pedro, Aveiro. Firstly, the 35 isolates were typed using molecular methods. Those methods consisted in ribossomal restriction of amplified DNA (ARDRA), Box-PCR and Pulse Field Gel Electrophoresis (PFGE). The results obtained revealed that the patients were already colonized by more than one genotype on admission suggesting a rapid dissemination of P. aeruginosa outside the hospital environment. PFGE revealed a high degree of heterogeneity between isolates. The results obtained suggested that cross contamination is an important route for P. aeruginosa acquisition. Type II topoisomerase (DNA gyrase and Topoisomerase IV) are the targets of quinolones. Mutations in the genes coding for these enzymes (gyrA, gyrB, parC and parE) were also studied. The results revealed the presence of mutations in 16 of the 35 strains. Some of the mutations found are new and have never been described before in P. aeruginosa. Those mutations were identified in the QRDR of gyrB gene, (codon 465) in the QRDR of parC gene (codon 35) and also in the parE gene (codon 431, 483, 487, 530, 538 and 544) Given the genetic background of the isolates, expression of the genes coding for membrane proteins involved in the efflux systems was also analysed. RT PCR showed that strain Pa31 was down regulated to mex B, mex F and mexY. A growth experiment was carried out on some strains showing QRDR mutations revealing that strain Pa31 shows a slower growth rate when compared to others. This is likely to have an impact on it’s in vivo fitness in antibiotic free medium.